Principals’ perceptions of public schools’ professional development changes during NCLB - Wieczorek, Douglas (Education Policy Analysis Archives, 2017)
This study investigated public school principals’ reports of professional development implementation at the school level while working in different state- and local-level contexts (state accountability level, geographic locations, socioeconomic status, demographics, and grade levels). I attempted to measure principals’ reported changes in levels of teacher involvement and alignment of professional development with standards, student learning outcomes, school goals, resources, and district goals during No Child Left Behind (NCLB). Using two-level, Hierarchical Generalized Linear Proportional Odds modeling (HGLM-PO), and three pooled waves of a national sample from the Schools and Staffing Survey (National Center for Education Statistics, 2000, 2004, 2007), I implemented a quantitative, repeated cross-sectional, self-report, extant secondary survey analysis design. Principals reported a decrease in teachers’ planning and presentation of professional development during NCLB implementation across all settings, indicating a potential reduction in teachers’ participation in the professional development process. Principals who worked in urban, elementary, low-SES, and high minority school contexts were more likely to report teachers’ participation in the planning and presentation of professional development, but were also more likely to report an increase in the direction and alignment of professional development with school and district goals, standards, student achievement outcomes, and resources. There is evidence that a school community’s location, socioeconomic status, and school demographics plays a role in how schools may interpret accountability environments and implement teachers’ professional development. In all settings, school leaders need to purposefully focus on and retain collaborative professional development practices with teachers in the context of continued accountability pressures.